A survey on the reading preferences of Miriam High School Students - Letargo, Ma. Katrina Joy R. (1993)
This study analyzed the reading preferences of 242 Miriam High School students. Using a questionnaire, it examined the reading preferences of family members and students on books, magazines, newspapers, and comics. Findings of the study revealed that reading materials preferred by parents/family members are similar with those preferred by the student respondents and that most reading materials borrowed from the library are fiction books.